Genotype-by-environment interaction influencing sensory attributes and biochemical components of peanuts from China - Tang, Yueyi; Cao, Shining; Zhang, Chushu; Hu, Weidong; Zhou, Haixiang; Wang, Mian; Zhu, Lifei; Chen, Jing; Zhang, Jun; Zhang, Jiancheng (Frontiers in Plant Science, 2025)
BackgroundPeanuts are a vital global crop and healthy food, valued for their nutritional and physiological benefits. Their sensory attributes and biochemical composition, which determine taste and nutritional quality, are influenced by multiple factors. Thirteen peanut genotypes were cultivated across three locations using a randomized block design. This study presents the first application through combined ANOVA (analysis of variance) and the GGE (Genotype and Genotype by Environment) biplot in sensory attribute evaluation research. The primary objectives are to: (1) characterize the sensory attributes of the tested genotypes; (2) analyze the genotype-environment interaction (GEI) effects; and (3) screen optimal varieties (lines) adapted to specific environmental conditions.ResultsSignificant differences were observed among genotypes and locations, and the G×E interactions for sensory quality and biochemical components of the tested peanuts. In GGE bioplot analysis, S9 was the best performer with crunchiness, fineness, sweetness, and overall acceptability, and L10 was the best performer in Large-seeded genotypes in overall acceptability. S9, S25, HY20, HY33, and HY20 was the best genotype at 3 locations in sucrose, oleic acid, linoleic acid, palmitic acid, and oil, respectively. Weifang (WF) demonstrated potential for producing high-quality peanuts for processing. In addition, there is an evident correlation between the biochemical components of peanut raw kernels and the sensory quality of roasted kernels. Among them, high-oleic peanuts exhibited superior crunchiness, sweetness, and roasted flavor, while high-oil varieties were less sweet with weaker flavor. High-protein peanuts were sweeter but more delicate. Proanthocyanidins positively correlated with bitterness/off-flavor and negatively with crunchiness, sweetness, and acceptability. High vitamin E reduced roasted flavor intensity.ConclusionGenotype, environment, and their interactions significantly impact peanut sensory and nutritional traits. High oleic acid and low proanthocyanidin content are critical for desirable sensory quality in this study. Lines S9 and L10 provide genetic resources for breeding, while Weifang’s climate supports premium peanut production. This data guides peanut cultivation in similar latitudes/climates.